2022
DOI: 10.3389/fpls.2022.896436
|View full text |Cite
|
Sign up to set email alerts
|

Differential Responses to Salt Stress in Four White Clover Genotypes Associated With Root Growth, Endogenous Polyamines Metabolism, and Sodium/Potassium Accumulation and Transport

Abstract: Selection and utilization of salt-tolerant crops are essential strategies for mitigating salinity damage to crop productivity with increasing soil salinization worldwide. This study was conducted to identify salt-tolerant white clover (Trifolium repens) genotypes among 37 materials based on a comprehensive evaluation of five physiological parameters, namely, chlorophyll (Chl) content, photochemical efficiency of PS II (Fv/Fm), performance index on an absorption basis (PIABS), and leaf relative water content (R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 93 publications
(107 reference statements)
0
3
0
Order By: Relevance
“…PI abs is a comprehensive index that reflects photochemical efficiency. Previous studies have indicated that the reduction in PI abs is more sensitive than F v /F m , accurately indicating the impairment of the plant’s photosynthetic machinery and the decrease in photochemical efficiency under adverse condition ( Chen et al., 2021 ; Li et al., 2022b ). The decrease in P n due to NaCl stress was influenced by both stomatal-limiting and non-stomatal-limiting factors.…”
Section: Discussionmentioning
confidence: 98%
“…PI abs is a comprehensive index that reflects photochemical efficiency. Previous studies have indicated that the reduction in PI abs is more sensitive than F v /F m , accurately indicating the impairment of the plant’s photosynthetic machinery and the decrease in photochemical efficiency under adverse condition ( Chen et al., 2021 ; Li et al., 2022b ). The decrease in P n due to NaCl stress was influenced by both stomatal-limiting and non-stomatal-limiting factors.…”
Section: Discussionmentioning
confidence: 98%
“…Exogenous magnesium can also maintain K + homeostasis in cells. Some studies suggest that the gene expression of POT/HAK family members may be directly regulated by the cytosolic Ca 2+ level under salt stress [56]. SKORs participate in the absorption and transportation of potassium from roots, which may regulate the salt tolerance of plants [57].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, high EL level and overaccumulation of MDA are two main indicators of cold injure in plants, as EL or MDA indicates cell membrane stability or membrane lipid peroxidation, respectively (Blum & Ebercon, 1981; Dhindsa et al., 1981). Previous studies have used Chl, Fv/Fm, PI ABS , EL, or MDA to evaluate and identify genotypic variation in tolerance to various abiotic stresses such as low temperature, high temperature, and salt stress (Li et al., 2022a, 2021; Zhang et al., 2011). A recent study demonstrated that bermudagrass experienced quick declines in Chl content, Fv/Fm, and PI ABS under chilling stress (Zhou et al., 2022).…”
Section: Discussionmentioning
confidence: 99%